(3GdeFI GdNGeSI ef GdeLGdS GdeDjOjIs
(3ChdgG (B:s
(3GdMeO ddg GdPj dG JYdb HChdjGA OjfI GdfbGFV Hd ceGdge Jced GdfahS GdfhGbU s
(3BNQgG (B:s
(3hYjf GdfLGI GdYjGfJeJ GdeGFI GdNGeSI HYhf Gddg hJhajbg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdEeHQhRjGfG (B(H 115) s
Keywords: (3GdJhMjO hGdedd hGdfMds